2022
DOI: 10.3390/foods11091238
|View full text |Cite
|
Sign up to set email alerts
|

Foodomics: Current and Future Perspectives in Food Analysis

Abstract: Climate change, an increase in population, and the recent pandemic crisis triggered by SARS-CoV-2 have all contributed to a period of global problems [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In recent years, the authenticity of a variety of food commodities has been developed using omics‐based technologies, which are linked to the power of powerful and enormous molecular tools and can help get around the constraints of existing approaches (Balkir et al, 2021; Kafantaris et al, 2020; Zhao et al, 2022). In particular, foodomics uses a variety of omics technologies (genomics, transcriptomics, proteomics, and metabolomics) to offer molecular data on the various expression levels (i.e., gene, transcript, protein, or metabolite), as well as to integrate these data from a systems biology viewpoint (Afzaal et al, 2022; Rodríguez‐Carrasco, 2022; Theodoridis et al, 2021; Valdes et al, 2022). Recent reports have shown that foodomics techniques using tools from the proteomics, genomics, and metabolomics domains can provide precise and trustworthy traceability systems (Balkir et al, 2021; Valdes et al, 2022).…”
Section: Role Of Advanced Foodomics In Food Traceabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the authenticity of a variety of food commodities has been developed using omics‐based technologies, which are linked to the power of powerful and enormous molecular tools and can help get around the constraints of existing approaches (Balkir et al, 2021; Kafantaris et al, 2020; Zhao et al, 2022). In particular, foodomics uses a variety of omics technologies (genomics, transcriptomics, proteomics, and metabolomics) to offer molecular data on the various expression levels (i.e., gene, transcript, protein, or metabolite), as well as to integrate these data from a systems biology viewpoint (Afzaal et al, 2022; Rodríguez‐Carrasco, 2022; Theodoridis et al, 2021; Valdes et al, 2022). Recent reports have shown that foodomics techniques using tools from the proteomics, genomics, and metabolomics domains can provide precise and trustworthy traceability systems (Balkir et al, 2021; Valdes et al, 2022).…”
Section: Role Of Advanced Foodomics In Food Traceabilitymentioning
confidence: 99%
“…Consequently, advanced high‐resolution analytical techniques with high separation capacity are required in metabolomics studies (Rodríguez‐Carrasco, 2022; Valdes et al, 2022). Some of the analytical instruments that are coupled and used for metabolite analysis include NMR coupled with gas chromatography (GC‐NMR), liquid chromatography (LC‐NMR), and solid‐phase extraction (LC‐SPE‐NMR).…”
Section: Role Of Advanced Foodomics In Food Traceabilitymentioning
confidence: 99%
“…It offers a comprehensive view of the functional proteins present, which is crucial for understanding various biological processes. These methodologies permit the detection of food parasites [11], food authenticity investigation [12], food microorganism detection [13], recognition of food allergens [14], food processing analysis [15], by-product safety [16] and systems biology studies [17], among others [18]. Thus, these approaches are a beneficial proposal for food science findings, where agencies, investigation laboratories, food companies, and controlling institutions are merging efforts to obtain essential understandings about food safety.…”
mentioning
confidence: 99%